Treatment motivation in adolescent girls with obesity - A. S. Votineva; Zh. V. Prokhorova; V. M. Polyakov; I. A. Cherevikova (Acta Biomedica Scientifica, 2024)
Background. The prevalence of obesity among children is increasing, which is a serious healthcare problem. In healthcare, the problem of motivation affects an important area that reflects its effectiveness – patient motivation for treatment. A decrease in treatment motivation reduces therapeutic effect, increases the complication rate of the underlying disease, reduces the quality of life of patients and increases treatment costs.The aim of the work. To identify the differences in treatment motivation in adolescent girls with obesity.Materials and methods. The pilot study was carried out at the clinic of the Scientific Centre for Family Health and Human Reproduction Problems. The study included 40 girls aged 14–16 years suffering from grade 1 obesity. To study treatment motivation, we used the following methods: J. Nuttin’s, D. McClelland’s, S.R. Panteleev’s, J.K. Collins’, method of the self-conception research, the “Type of Attitude Towards the Disease” method; attitude towards the disease.Results. The study showed that the adolescents who were admitted into hospital for the first time had higher treatment motivation during the study than the adolescents who were readmitted into hospital. The adolescents who were readmitted into hospital felt guilty remorse, anxious suspiciousness, and fear of failure. The dominant type of treatment motivation in both groups consisted of the following attitudes: achieving symptomatic improvement; receiving a “secondary gain” from the disease; other motivation (passive position).Conclusion. The obtained data from the study of treatment motivation in adolescent girls with obesity can be used to optimize the process of therapy of such patients in a hospital setting.